Craniocervical Junction Vertebral Artery Dural Arteriovenous Fistula With Cranial and Spinal Venous Reflux: 2-Dimensional Operative Video. Issue 5 (17th July 2019) - Patel, Krunal; Olijnyk, Leonardo Desessards; Tsang, Anderson Chun On; Pereira, Vitor Mendes; Radovanovic, Ivan
Abstract: Dural arteriovenous fistulae at the craniocervical junction are rare. When present together with spinal and cranial venous reflux they can have an aggressive natural history with hemorrhage or progressive myelopathy from venous congestion. In this operative video we demonstrate key steps in the surgical ligation of a dural arteriovenous fistula supplied by meningeal branches of the V4 segment of the vertebral artery. Informed consent was obtained. The patient was positioned prone with chin tucked. Utilizing a midline suboccipital craniotomy and removal of the arch of C1, the vertebral artery was identified at its V4 segment at it transitions from extra to intradural. The video illustrates how a midline approach can be used to access this lesion and a far lateral approach is not required to access the vertebral artery and its dural branches at the craniocervical junction. Division of the denticulate ligaments and mobilization of the spinal accessory nerve allows visualization of the proximal portion of the draining vein. Important anatomy in this region is demonstrated. The critical use of indocyanine green (ICG) dye is demonstrated as the first 2 clip applications were not proximal enough to obliterate the proximal draining vein and persistent early venous reflux was still seen on ICG. The importance of access to and obliteration of the proximal draining vein is shown. An intraoperative ICG and postoperative angiogram demonstrates complete occlusion of the dural arteriovenous fistula. In this case the patient had minor sensory deficits postoperatively which were resolved by 6 wk postoperatively.